2020
DOI: 10.32479/ijefi.10674
|View full text |Cite
|
Sign up to set email alerts
|

Terrorism and International Tourism Nexus: Evidence From Pakistan

Abstract: The association among terrorism and tourism is crucial from the macroeconomic perspective as tourism is considered as a vital sector regarding developmental impacts. This analysis conducted to extract the influence of terrorism on tourism in Pakistan, expending the latest dataset and incorporating some additional factors like FDI, human capital, and economic growth for 1980-2016, using ARDL bounds test. The evidence shows that terrorism has an inverse relationship with tourism in the long run that is statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…Terrorism-related attacks are not only aimed at targeting the victims but also sending a message of fear among communities ( 51 ). Hence, the population is confronted with developing a substantial number of long-term problems imposed by terrorism-related disasters ( 52 ). Data reveals that 18 - 50% of post-traumatic stress disorder (PTSD) were found prevalent among the victims of large-scale terrorism-related events ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…Terrorism-related attacks are not only aimed at targeting the victims but also sending a message of fear among communities ( 51 ). Hence, the population is confronted with developing a substantial number of long-term problems imposed by terrorism-related disasters ( 52 ). Data reveals that 18 - 50% of post-traumatic stress disorder (PTSD) were found prevalent among the victims of large-scale terrorism-related events ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies including Samitas et al (2018) have shown that terrorism slows down visitors to Greece by using analysis of principal components to create a tourism-related proxy. Besides, Rauf et al (2020) looked into the links between terrorism and travel in Pakistan. According to the study, terrorist attacks eventually discourage people from travelling.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Pakistan is an attractive tourist destination due to its cultural, religious, adventure, and geographic tourism sites. However, due to terrorism, tourism became adversely affected from 2000 to 2017 [58,59] and presently tourism is in the renaissance phase [60] and lacks sustainability.…”
Section: Tourism In Pakistanmentioning
confidence: 99%